Critical Teaching In Tesol: A Retrospective Analysis Of The Problems Of Programming And Opportunity - Ghafar, Zanyar; Lestari, Ayu; Falah, Zidnal (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
This study examines the problems instructors, and students face while doing critical work in the TESOL sector. It is possible to quickly study several articles written a few years ago to see the usefulness of this topic by examining those written at the time. The abstract of an article by (Joseph Jeyaraj & Harland, 2016) Jeyaraj and Tony Harland from 2016 titled "Teaching with Critical Pedagogy in ELT: the Problems of Indoctrination and Risk" shows reports about higher education experiences in English that are familiar with as a relative environment of the pedagogues. The objective was to identify the main difficulties with critical pedagogy. Thirteen instructors from higher education institutions from across the globe were interviewed to understand this practice better, and all had a clear objective for social justice. The second piece is titled "Becoming a Critical Language Teacher" and was authored by (MORGAN, 2014)r, as the item's abstract assumed. The author seeks a specific lesson in critical abilities to address the difficulties of applying critical theories with Western roots in Chinese contexts. This article's last section looks at the effects of this activity on various perceptions of the crisis in language education. The third article, titled "Challenges in Critical Language Teaching," written by (Goiânia, Goiás, in 2012), is focused on the idea that language teachers must become fully knowledgeable of academic voice, subject choice and length, and the idea of language as a social practice in order to adopt critical education. The last one, "Being and Becoming TESOL Educators: Embodied Learning via Practicum," by Martin Andrew and Oksana Razoumova in 2017, explained that during placement exercises in terms of increasing learners' knowledge and skills, increasing their reliance and self-confidence, and helping them to grow as educators and individuals, their professional and social identities. The researchers employed several reliable, practical materials instead of inaccurate survey data. These findings highlight how important during the preparation phase; instructors should be prepared to deal with regular and unexpected discoveries. They should also execute and demonstrate practical work, promote the value of embodied learning, and adopt it as a practice.